KEMAMPUAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS XI SMK MUHAMMADIYAH 1 PONTIANAK - Riska Yuliani; Nanang Heryana; Syambasril Syambasril (Universitas Tanjungpura, 2020)
Abstract This study generally discussed the class XI of SMK Muhammadiyah 1 Pontianak students’ skills in writing the explanation text and specifically discussed their skills from the aspects of accuracy of text type, structure, language rules, and accuracy of spelling and punctuation. This study aims to describe the skills in writing a explanation text on the class of SMK Muhammadiyah 1 Pontianak in academic year 2019/2020. his research implemented a descriptive study with the form of quantitative and qualitative. The sample was taken using a random sampling technique. The data was collected using indirect communication with the data collection tool in the form of a written test. The results of the analysis showed that the students' writing skills, according to the aspect of the accuracy of the type of text were categorized as very good at 98.6%. In the structural aspect of the general statement section with a very good category of 89.5%, the structure of the explanation section with a very good category of 90.2%, the structure of the interpretation section with an excellent category of 92.3%, the aspect of linguistic principles with a moderate category of 66%, and the aspect of accuracy of writing spelling and punctuation with very good category was 82%. Keywords: Explanation Text, Text Structure, Linguistic Principles, Writing Spelling and Punctuation